Study of ZnO Nanospheres Fabricated via Thermal Evaporation for Solar Cell Application - Alia Azmi, Fatin Farisha; Sahraoui, Bouchta; Muzakir, Saifful Kamaluddin (UI Scholars Hub, 2019)
A solar cell is a device that absorbs light energy to generate electrical energy. A typical example of a solar cell is the quantum dot solar cell (QDSC), which consists of three main components: (i) fluorophore: the component that absorbs light and generates excited state electrons and holes, (ii) photoelectrode: the component that transports the excited state electron and prevents recombination of excited state electrons and holes, and (iii) electrolyte: the component that re-plenishes the vacancy left by the excited electron in the hole. Despite the increasing number of research in the QDSC field, to date, a device with significant photovoltaic efficiency has not been developed. In this study, the mechanism of electron transport in a zinc oxide (ZnO) photoelectrode was investigated. Two ZnO layers were fabricated using thermal evaporation method at different vacuum pressures (5 × 10-4 and 5 × 10-5 Torr). Two solar cells were fabricated using ZnO as photoelectrode, lead sulphide as fluorophore, and a mixture of carboxymethyl cellulose and polyvinyl alcohol as electrolyte. The cell which utilized the ZnO fabricated under 5 × 10-5 Torr showed the highest efficiency ( = 0.98%), with fill factor = 22.07%, short circuit current = 2.85 mA/m2, and open circuit voltage = 80.719 mV.